Two Clinically Unusual Cases of Folliculotropic Mycosis Fungoides: One with and the Other without Syringotropism - SEÇKİN GENÇOSMANOĞLU, DİLEK (KOREAN DERMATOLOGICAL ASSOC, 2014)
Mycosis fungoides is the most common form of cutaneous T-cell lymphoma, and it rarely exhibits predilection for hair follicle and eccrine gland infiltration. Here, we present 2 similar cases that display folliculotropism with varying amounts of follicular mucinosis, with and without syringotropism. The features observed in both cases were cystic, comedo-like, acneiform lesions; generalized involvement with loss of body hair; pruritus; and hidradenitis suppurativa-like lesions. Hypohidrosis as well as nail and palmoplantar involvement with lichen planopilaris-like clinical features were unique characteristics of the first case. Despite the well-known aggressive behavior of follicular mycosis fungoides, the presented cases had a subtle, slowly progressive, but persistent, clinical course. Folliculotropic and syringotropic mycosis fungoides are variants of cutaneous T-cell lymphoma. Clinical presentations might be challenging, and multiple, deep biopsy specimens containing adnexal structures are required for this critical diagnosis. Aggressive treatment may not be necessary in cases having an indolent course, especially in those with syringotropism.
Keywords: Adnexal; Eccrine gland; Follicle; Lymphoma; Mycosis fungoides; Neoplasm; T-CELL LYMPHOMA; CUTANEOUS-LYMPHOMAS; SEZARY-SYNDROME; ECCRINE GLAND; CLASSIFICATION; INFILTRATION; PLANTARIS; MUCINOSIS; SPECTRUM; PALMARIS